Conversionary Protestants do not cause democracy - Elena Nikolova; Jakub Polansky (Global Labor Organization (GLO), 2020)
In "The Missionary Roots of Liberal Democracy", Robert D. Woodberry (2012) claims that the emergence of stable democracies around the world was influenced by conversionary Protestantism. While Woodberry's historical analysis is exhaustive, the accompanying empirical evidence suffers from severe inconsistencies. We replicate Woodberry's analysis using 26 alternative democracy measures and extend the time period over which the democracy measures are averaged. These two simple modifications lead to the breakdown of Woodberry's results. We find no significant relationship between Protestant missions and the development of democracy, which raises concerns about the robustness and broader applicability of Woodberry's findings. We discuss some alternative explanations for Woodberry's results which we hope can inform future research on this topic.
Keywords: H11; N40; Z12; 330; religion; democracy; economic history; political institutions